RANCANG BANGUN ALAT PEMBAGI CONTOH KERJA BENIH MENTIMUN (Cucumis sativus L.) BERBASIS MIKROKONTROLER Design of Microcontroller-Based Seeds Sample Divider for Cucumber (Cucumis sativus L.) - Ayu Nur Litasari; Budi Wijayanto; Geraldo Adinugra Rimartin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to design and construct a microcontroller-based seed sample divider for cucumber (Cucumis sativus L.), to evaluate its technical performance, and to compare its result with those of the conventional soil divider method. The study was conducted from November 2025 to April 2026 at the Seed Machinery Laboratory (Alsinben), Yogyakarta-Magelang Agriculture Development Polytechnic. The device was constructed using an Arduino Uno Atmega328P microcontroller as the central control unit, load cell sensors with HX711 signal amplifier modules for mass measurement, an SG90 servo motor as the actuator for directing seed flow, and a 16 x 2I2C LCD as the display interface. The seed division process followed the dividing tree method, with an initial submitted sample weight of 150 gram and a working sample target of 70 gram, in accordance with ISTA (2025) standards. Performance was assessed using three parameters: division accuracy, coefficient of variation (CV), and total mass deviation. The results showed that the microcontroller-based device achieved a seed division accuracy of 99,8%, which was higher than the 97,6% obtained by the manual method. The average CV values for containers A and B in the microcontroller-based device were 1,14% and 1,36%, respectively, lower than those of the manual device at 4,64% and 3,41%. The total mass deviation of the microcontroller-based device was recorded at 0,13%, considerably lower than the manual device at 3,37%. All performance parameters of the microcontroller-based device met the standards setablished under ISTA (2025) and SNI ISO/IEC 17025:2017.